Faktor-Faktor yang Mempengaruhi Minat Nasabah untuk Menabung di Bank Muamalat Cabang Cikarang - Kristina Salindri; Deni Lesmana (Jurnal Al-fatih Global Mulia, 2022)
Bank Muamalatis the first commercial bank inIndonesia to implement Islamic sharia principles inconducting its operations. Established in 1991, initiated by the MUI and the Government of Indonesia, and commenced operations in 1992, supported by Muslim scholars and businessmen well as the wider community. The purpose of this study is to determine whether there is influence of services, influence sharing and location to customer interest. The population of this study is that the data obtained from the questionnaire Muamalat customer savings with the sample are 70 respondent. This study uses a quantitative approach to the data measured by questionnaires distributed to customers Muamalat interest associated. The technique of data analysis uses the double analysis regresi with the program SPSS 23 Version to see the aim of connection. The question that used for this research has been tested in reliability and validity with reliability and validity tested, and the instruments are reliable and valid as a measuring instrument. The results of this study, partially that services (0.008) and location (0.000) have a significant effect on customer interest at PT Bank Muamalat Branch Cikarang. But variable influence sharing have not significant effect on customer interest with value of significant 0.228.